The Effectiveness of Community-Based Health Promotion Strategies in Improving Healthy Living Behaviors; SYSTEMATIC LITERATURE REVIEW - Daniela Rolandia Maria Umbelina Fernandes; Hermenegildo Pereira; Arlindo Fátima; Carlos dos Santos; Levi Anatolia S.M. Exposto (YCMM, 2026)
This study aims to know The Effectiveness of Community-Based Health Promotion Strategies in Improving Healthy Living Behaviors. The research method used a systematic review literature approach by analyzing scientific articles published in the 2021-2025 period. Articles were selected based on inclusion and exclusion criteria. Health promotion effectively improves Clean and Healthy Living Behavior (PHBS) by increasing knowledge, awareness, and healthy daily practices at individual and household levels. Social media and community-based interventions, supported by advocacy and empowerment, enhance behavior change and participation. However, challenges such as misinformation, limited participation, and digital inequality reduce effectiveness. Complex behaviors require multi-level structural and system support. Therefore, sustainable and integrated health promotion programs are essential for long-term behavioral change and improved public health outcomes. Conclued that Health promotion is effective in improving healthy living by increasing knowledge and encouraging healthy daily behaviors at individual and household levels. Social media and community-based approaches, supported by advocacy and diverse communication tools, enhance behavior change and community participation.